Surgical Capacity Assessment and Leverage in the Palestinian Land (SCALPEL-I) Study: The First Nationwide Plastic Surgery Capacity Evaluation in Palestine - Osaid Alser, MD, MSc(Oxon); Laith Ayasa, MD; Mohammed Alhabil, MD; Shahd Idais, MD; Ayah Almzayyen, MD; Majdeddin MohammedAli, MD; Reem Younes, MD; Heba Alghoul, MD; Muath Alser, MD; Bryce Stash, MD; Roba Khundkar, MD; Timothy Goodacre, MD; et al. (Plastic and Reconstructive Surgery, Global Open)
Background:. Access to surgical care in low-to-middle-income countries (LMICs), especially in war-torn areas such as the occupied Palestinian territory (oPt), is a global health priority. The plastic surgical capacity in the oPt has not been evaluated. This study provides the first systematic evaluation of plastic surgical capacity in the oPt. Methods:. A cross-sectional study conducted between December 2022 and February 2023 included facilities providing plastic surgery services in the oPt, except private centers run by nonsurgeons. A modified PIPES (personnel, infrastructure, procedures, equipment, and supplies) tool was used. Data were analyzed for geographic and private/public disparities. Results:. Eleven facilities were included; 6 (54.5%) were in the West Bank and 5 (45.5%) in Gaza. The majority were private hospitals (n = 6, 54.5%). The mean PIPES score was personnel = 4.3 (4.03), infrastructure = 18.4 (2.4), procedures = 9.8 (3.8), equipment = 19.2 (3.6), and supplies = 22.4 (1.9). Hospital beds, operating rooms, and plastic surgeons per 100,000 people were 33.5, 1.0, and 0.5, respectively. There were 8 board-certified plastic surgeons. No facilities had a plastic surgery residency program. Key deficiencies included: 8 facilities (72.2%) not performing microsurgical free tissue transfers (none in Gaza), 5 (45.5%) lacking a system to identify complications, and 7 (63.3%) not offering regular educational courses. Average power supply was 8.0 hours/day in Gaza and 24.0 hours/day in the West Bank. Conclusions:. Plastic surgical capacity in the oPt shows significant deficiencies, especially in Gaza. These findings should inform stakeholders to address disparities, develop training programs, and improve access to safe plastic surgery.